Cultivation of Pleurotus sajor-caju (Fr.) Singer on Metroxylon sagu Rottb. Bark and Frond - Haslinza, Senghie (Universiti Malaysia Sarawak (UNIMAS), 2021)
Sawdust (SD) is a commercially used fruiting substrate component for the cultivation of Pleurotus sajor-caju (grey oyster mushroom) in Malaysia. However, due to the declining sawdust supply, this study was done to examine the possibility of using sago palm bark (SB) and sago palm frond (SF) as alternative base carbon sources in the fruiting substrate used as compared to sawdust. Nine substrate ratio mixtures were studied, including sawdust alone as a control and the combination of 25:75, 50:50, and 75:25 ratios between SD and SB or SF for mushroom cultivation of grey oyster mushroom. Mushroom cultivation techniques were conducted in the mushroom house. The lignocellulosic (lignin, cellulose, and hemicellulose) content for the substrate ratio mixtures was analysed alongside the pH value, extractives, ash, and moisture contents using standard methods. The singular substrate, 100SB, showed the highest hemicellulose content (60.7%), while the combination of 50SD:50SF substrate contained the highest lignin (40.7%). For cellulose, 75SD:25SF had a higher percentage at 46.2% compared to others. Singular substrate 100SB had the highest moisture content (11.7%). For extractives content, singular substrate 100SD had the lowest (2.9%). Ash content (1.4-5.2%) and pH value (4.7-6.1%) were significantly different from each other. For morphological characteristics, cap diameter (6.7-8.4 cm), stipe length (6.1-7.5 cm), and the number of effective fruiting bodies/bunch in different substrate ratio mixtures (1.7-2.2) were recorded in this study. The results showed a significant difference in the total colonization period, total sporocarp yield, and biological efficiency (BE) for singular substrate and substrate in combination. Singular substrate 100SB and 100SF gave a comparable performance as 100SD. For substrate in combination, 50SD:50SF is the most suitable ratio as a supplement to sawdust for the cultivation of P. sajor-caju. Singular substrate 100SD achieved a faster total colonization period (24.44 days) than other substrates and obtained the fastest first harvest (50.33 days). The substrate in combination 50SD:50SF produced a higher total yield (88.09 g/bunch) and higher BE (17.62%) with a short total colonization period (26.45 days). The substrate containing SB and SF produced high values in cap diameter, stipe length, and effective fruiting bodies. Both singular and in combination tested, sago bark and frond showed good potential to be used as fruiting substrates for the cultivation of P. sajor-caju based on mycelial and sporocarp yield. These substrate ratio mixtures, as compared to sawdust, SB, and SF are as singularly and in combination with SD were comparable with SD and would be a good alternative for the growers of P. sajor-caju for mushroom cultivation.